Contradictions in and improvements to urban and rural residents' housing rights in China's urbanization process. (March 2020) - Lyu, Ping; Yu, Miao; Hu, Yuanrui
Abstract: Objective: Increasing differences between urban and rural residents' housing rights not only affect the implementation of rural revitalization strategies but also affect the quality of urbanization. Based on relative deprivation theory and Pareto optimality, this study investigated this problem and, combined with a practical summary of the reform of the homestead system, explored ways to solve the disparities between urban and rural residents' housing rights, aiming to provide a basis for policy adjustments. Methods: Theoretical analysis and case study were used for this research. Results: There are significant disparities in the housing rights of urban and rural residents. Urban and rural residents have a strong sense of relative deprivation, which is not conducive to the stable development of urban and rural society. On the basis of 15 pilot cases of rural homestead reform, we found that a large gap exists between the housing rights of rural and urban residents and that the gap differs among different pilot areas. An integrated urban–rural housing system could significantly improve the housing rights of rural residents, facilitate Pareto optimization, and reduce the sense of relative deprivation between urban and rural residents. Conclusion: Creating a new rural housing system and promoting the construction of an integrated urban–rural housing system would help promote equality in the housing rights of urban and rural residents. Such a system could also help improve the housing utility of urban and rural residents and integrate urban and rural development.